2021
DOI: 10.1159/000518969
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Overexpression of Neurosecretory Protein GL Leads to Obesity in Male C57BL/6J Mice

Abstract: <b><i>Introduction:</i></b> The mechanisms underlying obesity are not fully understood, necessitating the creation of novel animal models for the investigation of metabolic disorders. We have previously found that neurosecretory protein GL (NPGL), a newly identified hypothalamic neuropeptide, is involved in feeding behavior and fat accumulation in rats. However, the impact of NPGL on obesity remains unclear in any animal model. The present investigation sought to elucidate whether NPGL … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Sugar is the root cause of many diseases, such as metabolic syndrome, via dysfunction of systemic energy metabolism. We recently showed that hypothalamic overexpression of Npgl, a novel precursor gene encoding a small protein, induces obesity by enhancing the palatability of carbohydrates in rodents [15,20]. However, the difference in lipogenic efficiency of NPGL with different types of sugars remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sugar is the root cause of many diseases, such as metabolic syndrome, via dysfunction of systemic energy metabolism. We recently showed that hypothalamic overexpression of Npgl, a novel precursor gene encoding a small protein, induces obesity by enhancing the palatability of carbohydrates in rodents [15,20]. However, the difference in lipogenic efficiency of NPGL with different types of sugars remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NPGL promoted the intake of carbohydrate and fat accumulation via de novo lipogenesis in rats [15,19]. Moreover, overexpression of the NPGL-precursor gene (Npgl) rapidly induced obesity in mice [20]. Thus, we speculate that NPGL exerts obesogenic effects by evoking the palatability of sugars in birds and mammals.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our previous studies have indicated that NPGL participates in energy homeostasis, including feeding behavior and fat accumulation in rodents [ 28 , 29 , 30 , 31 ]. In addition, we found that NPGL cell bodies are localized in the ArcLP, and NPGL-containing fibers project to several anterior hypothalamic regions in mice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Npgl mRNA expression is increased by fasting in mice, whereas it is reduced by a high-fat diet [ 29 ]. In addition, the administration of NPGL and Npgl overexpression in the hypothalamus increases food intake and fat accumulation in rats and mice [ 28 , 30 , 31 ]. These data suggest that NPGL is involved in the energy metabolism of rodents.…”
Section: Introductionmentioning
confidence: 99%